Linear Stability Analysis of Relativistic Magnetized Jets: The Minimalist Approach - Vlahakis, Nektarios (2024)
A minimalist approach to the linear stability problem in fluid dynamics is developed that ensures efficiency by utilizing only the essential elements required to find the eigenvalues for given boundary conditions. It is shown that the problem is equivalent to a single first-order ordinary differential equation, and that studying the argument of the unknown complex function in the eigenvalue space is sufficient to find the dispersion relation. The method is applied to a model for relativistic magnetized astrophysical jets.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; galaxies: jets; INSTABILITIES; ISM: jets and outflows; magnetohydrodynamics (MHD); mathematical physics; methods: analytical; relativistic processes